2014
DOI: 10.1089/fpd.2014.1808
|View full text |Cite
|
Sign up to set email alerts
|

Organic or Antibiotic-Free Labeling Does Not Impact the Recovery of Enteric Pathogens and Antimicrobial-ResistantEscherichia colifrom Fresh Retail Chicken

Abstract: We investigated the implied health benefits of retail chicken breast labeled as "organic" or "antibiotic-free" when compared to conventional products based on frequency of contamination by Salmonella spp., Campylobacter spp., and coliform bacteria resistant to fluoroquinolones, extended-spectrum cephalosporins, or carbapenems. We purchased 231 prepackaged chicken breasts from 99 grocery stores representing 17 retail chains in Ohio, Michigan, and Pennsylvania from June to September 2012. Ninety-six (41.5%) pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 45 publications
3
32
1
Order By: Relevance
“…In both the latter study and the present one, the absence of a protective effect of "all natural" and/or "no antibiotics" labeling suggests that such labels may not accurately reflect the actual antibiotic exposure of the source chickens. Alternatively, specific aspects of organic production, apart from its required absence of antibiotic use in chicks after the first day of life, may underlie the observed protective effect of the "organic" label claim against resistance, as documented here and by Mollenkopf et al (6).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In both the latter study and the present one, the absence of a protective effect of "all natural" and/or "no antibiotics" labeling suggests that such labels may not accurately reflect the actual antibiotic exposure of the source chickens. Alternatively, specific aspects of organic production, apart from its required absence of antibiotic use in chicks after the first day of life, may underlie the observed protective effect of the "organic" label claim against resistance, as documented here and by Mollenkopf et al (6).…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies, including several to which some of the authors of the present study contributed, have documented the presence of ExPEC and antimicrobial-resistant E. coli isolates in retail chicken, turkey, beef, and pork products (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Novel features of the present study include its extensive geographic range (previous studies based in the United States have been limited to four or fewer states [6,7,10]), its comparatively recent sampling frame (2013; the most recent similar study based in the United States was from 2012 [6]), and the extensive phylogenetic and clonal analysis performed on these isolates.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Van Overbeke et al (2006) found significantly higher prevalence in cecum (p=0.024) and duodenum (p=0.036) samples from organic compared to conventional broilers, but no difference in gastrointestinal tract prevalence. On retail level, two studies Mollenkopf et al, 2014) did not find a significant difference (p>0.05) and two studies (Cui et al, 2005;Hardy et al, 2013) did not mention significance levels.…”
Section: Broilersmentioning
confidence: 89%